Effect of Positive Parent Education Program - Park, Sung-Joo (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to reduce the stress of parenting and positively change the parenting attitude by using the positive parent education program based on problem solving counseling theory, which is one of the important theories of positive psychology. Through this, it can be said that it is meaningful to increase parental efficacy and subjective well-being by improving parents' positive thinking, positive emotion, and positive attitude in child rearing. To this end, this study aims to verify the effect on parents' parental efficacy and subjective well-being by implementing a positive parent education program developed on the basis of problem solving counseling theory, which is a theory of positive psychology.Methods/Statistical analysis: The subjects of this study were recruited after 1 month of guidance for parents of children aged 13 years. Ten of 20 positive parent education program applicants were randomly selected as 10 experimental groups and 10 control groups. The positive parent education program proposed in this study was conducted in the control group after the end of the experimental group program from the viewpoint of counseling ethics. The Positive Parent Education Program was conducted for its 8 sessions in total, twice a week, one and a half hours per session, for the 10 in the experiment group. No Positive Parent Education Program was conducted for the control group. A preliminary test was conducted for both the experiment group and control group, and then a post- test was conducted on the experiment group after the positive parent education program. Data Processing & Analysis Methods: To analyze test results, the independent t-test and nonparametric statistical analysis (Wicoxon Matched- Pairs Signed-Ranks Test) were conducted by means of SPSS 19.0 program.Findings: The positive parent education program showed a significant result from the pre-post test comparison in the experimental group than the control group in parent efficacy. In addition, the positive education program showed a significant result from the pre-post test comparison in the experimental group rather than the control group in subjective well-being.Therefore, I found that a positive parent education program worked.Improvements/Applications: Positive parent education programs have been effective in promoting parental efficacy and subjective well-being, so they can be used in various parent education programs. It is also effective in lowering parenting stress and negative viewpoints, raising positive parenting attitudes and happiness, and promoting the relationship with positive children to create a healthy and happy family.